Metode Tahfizh Hadis di Kalangan Peserta Hifzhil Hadis pada Musabaqah Tilawatil Quran Tingkat Provinsi Sumatera Barat Ke-40 Tahun 2023: - Situngganai (Jurnal Riset Agama, 2025)
This study is based on the importance of preserving the hadiths of the Prophet Muhammad SAW through tahfizh activities, particularly in the Hifzhil Hadith branch of the 40th West Sumatra Provincial Musabaqah Tilawatil Qur’an (MTQ) in 2023. The main issue of this study is the diversity of tahfizh methods used by MTQ participants. The purpose of this study is to examine the hadith tahfizh methods used by participants, analyze their strengths and weaknesses, and examine the relationship between these methods and the concept of tahammul wa al-adā’ al-ḥadis. This study uses a qualitative method with a descriptive-analytical approach. Data were obtained through interviews, observations, and documentation of the participants, trainers, and organizers of the 40th West Sumatra MTQ in 2023. The results of this study indicate that there are 11 methods of hadith memorization used by participants in the Hifzhil Hadith category at the 40th West Sumatra Provincial MTQ in 2023, namely the talaqqi, tikrar, qira’ah, talqin, muroja’ah, tafahhum, random, grouping A’la narrators, kitabah, memorizing per sentence, and applying the content of the hadith. Each method has its advantages and disadvantages. The relationship between the hadith memorization methods and the concept of tahammul wa al-ada’ al-ḥadis is functional, not structural. This means that not all memorization methods are directly rooted in the classical tahammul wa al-ada’ system, but some methods still have relevance in the spirit and basic principles of hadith narration.